Effect of root pruning on the root growth potential (RGP) of three Philippine native tree species - Burcer, Paola Andrea R.; Carandang, Wilfredo M.; Gascon, Antonio F.; Tiburan, Cristino L. Jr (Philippine Journal of Science)
"Root growth potential (RGP) is the plant's capacity to grow new roots, an important trait for seedlings to be used on any reforestation program. In the Philippines, these kinds of programs often end up in failure, as low-quality seedlings are usually chose due to unfamiliarity with attributes that indicate good outplanting performance, narrow sources of high-quality seeds, and the lack of a reliable quality assessment method. This study aimed to determine the RGP of three native species- namely, bignai(Antidesma bunuis), kamagong (DIospyros blancoi), and molave (Vitex parviflora)-and find its correlation with other morphological parameters"-title page.